Forensic genetic genealogy using microarrays for the identification of human remains: The need for good quality samples – A pilot study. (May 2022) - Davawala, A.; Stock, A.; Spiden, M.; Daniel, R.; McBain, J.; Hartman, D.
Abstract: The successful application of forensic genetic genealogy (FGG) to identify Jane and John Doe cases in the United States has raised the prospect of using the technique in Australia to assist in the reconciliation of unidentified human remains (UHRs) with long term missing persons. A study was conducted to explore the feasibility of FGG using whole genome array (WGA) data from both pristine control samples as well as compromised casework samples, with the view to explore how DNA quantity and quality impacted on the ability to generate search results when compared to a genetic genealogy database, such as GEDmatch. From this study, several insights were gained as to the impact DNA quantity and degradation had on the percentage of SNPs genotyped and heterozygote/homozygote ratio – which are critical for successful matching outcomes. It was noted in this study (using a control sample) that successful matching occurred when genotyping errors were 5% or less. Two UHR cases were matched to kits on GEDmatch PRO, which provided investigative leads for identification purposes. The effectiveness of the FGG approach to match casework samples (as well as volunteer samples used in the study) is indicative of the usage of 'direct-to-consumer' (DTC) genetic testing by Australians. Given the (often) limited availability of casework samples, findings from this study will assist Australian agencies considering the use of FGG, to determine if WGA is a suitable method for their application.